Chinese Force Modernization and its Implications on the Region - Mr. Khusrow Akkas Abbasi (CISS Insight Journal, 2015)
China is engaged in a military modernization program that is continually enhancing the operational capabilities of the People’s Liberation Army (PLA). In order to achieve this objective PLA has worked to reduce its manpower and replace obsolete military hardware with more sophisticated systems since the 1980s. Operationalization of advanced systems in its air, land, sea and missile forces have increased the PLA’s military efficacy, specifically in the backdrop of its military doctrine of “Local War under Conditions of Informatization”. Induction of modern weapon systems in all its forces army, air force, navy and missile force, also known as ‘Second Artillery Force’ has necessitated changes in training and tactics as well. These developments have enhanced PLA’s capabilities and augmented its capacity to deliver, placing China among major military powers of the world. China’s comprehensive national policy, which articulates its strategic objectives and the means to achieve those objectives however, are unclear. It has maintained ambiguity in its claims over the entire South China Sea enclosed by what is call the ‘nine‐dash line’. China has also maintained ambiguity regarding its defence capabilities and expenditure.